A Survey Study of Pregnant Women and Healthcare Practitioners Assessing the Knowledge of Attitudes and Practices of Hepatitis B Management at a Teaching Hospital in Kumasi, Ghana, West Africa. (1st September 2015) - Cheng, Anita; Jose, JoAnn; Larsen-Reindorf, Roderick; Small, Christina; Nde, Helen; Dugas, Lara; Ehrhardt, Stephan; Nelson, Kenrad; Ezeanolue, Eche; Layden, Jennifer
Abstract: Hepatitis B virus (HBV) infection is a major global health problem, with sub-Saharan Africa (SSA), including West Africa, bearing a large proportion of cases. Mother-to-child and early childhood horizontal transmission, the most common mechanisms of disease spread in West Africa, lead to a high rate of chronic infection. Although these transmission mechanisms are preventable through vaccine and hepatitis B immunoglobulin, they are not routinely used due to limited resources. Antiviral therapy in pregnant women who are HBV positive is another option to reduce transmission. We conducted a survey study of pregnant women and clinicians at a teaching hospital in West Africa to determine the knowledge base about HBV and willingness to implement measures to reduce HBV transmission. Pregnant women had limited knowledge about HBV and the common transmission mechanisms. Clinicians identified cost and time as the major barriers to implementation of HBV prevention measures. Both pregnant women and clinicians were largely willing to implement and use measures, including antivirals, to help reduce HBV transmission.